The July 1st Event and Beyond - Human Rights Situation in Mongolia - Munkhzorig, B (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i15-16.36 Mongolian Journal of International Affairs No.15-16 2008-2009 pp.201-204